Automated assessment of EEG background for neurodevelopmental prediction in neonatal encephalopathy - Micheline Lagacé; Saeed Montazeri; Daphne Kamino; Eva Mamak; Linh G. Ly; Cecil D. Hahn; Vann Chau; Sampsa Vanhatalo; Emily W. Y. Tam (Annals of Clinical and Translational Neurology)
Abstract Objective Assess the capacity of brain state of the newborn (BSN) to predict neurodevelopment outcomes in neonatal encephalopathy. Methods Trends of BSN, a deep learning‐based measure translating EEG background to a continuous trend, were studied from a three‐channel montage long‐term EEG monitoring from a prospective cohort of 92 infants with neonatal encephalopathy and neurodevelopmental outcomes assessed by Bayley Scales of Infant Development, 3rd edition (Bayley‐III) at 18 months. Outcome prediction used categories “Severe impairment” (Bayley‐III composite score ≤70 or death) or “Any impairment” (score ≤85 or death). Results “Severe impairment” was predicted best for motor outcomes (24 h area under the curve (AUC) = 0.97), followed by cognitive (36 h AUC = 0.90), overall (24 h AUC = 0.84), and language (24 h AUC = 0.82). “Any impairment” was best predicted for motor outcomes (12 h AUC = 0.95), followed by cognitive (24 h AUC = 0.85), overall (12 h AUC = 0.75), and language (12 and 24 h AUC = 0.68). Optimal BSN cutoffs for outcome predictions evolved with the postnatal age. Low BSN scores reached a 100% positive prediction of poor outcomes at 24 h of age. Interpretation BSN is an excellent predictor of adverse neurodevelopmental outcomes in survivors of neonatal encephalopathy after therapeutic hypothermia, even at 24 h of life. The trend provides a fully automated, objective, quantified, and reliable interpretation of EEG background. The high temporal resolution supports continuous bedside brain assessment and early prognostication during the initial dynamic recovery phase.